A Contribution to the Understanding of Pain in Fibromyalgia Based on Cerebrospinal Fluid Investigations - Henning Værøy (Pain Research and Management)
Fibromyalgia is established in current practice as a condition with widespread pain and a number of specific tender points, as well as symptoms of limb stiffness, lack of refreshing sleep and depression. Musculoskeletal correlations with the syndrome have generally been disappointing. Chemical changes in the cerebrospinal fluid are of interest and seem to show significant relationships with fibromyalgia, both with respect to opioid peptides and substance P. The nature of these relationships and their possible linkage with neuronal plasticity at the spinal cord level are discussed. The influence of both peripheral sensitization and reduced presynaptic inhibitory feedback is considered in this connection.